Supersymmetric QCD corrections to e+e- → tb̄H- and the Bernstein-Tkachov method of loop integration - Kniehl, B. A.; Maniatis, Markos; Weber, Marcus Max (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
The discovery of charged Higgs bosons is of particular importance, since their existence is predicted by supersymmetry and they are absent in the standard model (SM). If the charged Higgs bosons are too heavy to be produced in pairs at future linear colliders, single production associated with a top and a bottom quark is enhanced in parts of the parameter space. We present the next-to-leading-order calculation in supersymmetric QCD within the minimal supersymmetric SM, completing a previous calculation of the SM-QCD corrections. In addition to the usual approach to perform the loop integration analytically, we apply a numerical approach based on the Bernstein-Tkachov theorem. In this framework, we avoid some of the generic problems connected with the analytical method.
Im Titel sind "+" und "-" jeweils hochgestellt
Gesehen am 10.10.2022